Forced Migration and Mortality - Thomas K. Bauer; Matthias Giesecke; Laura M. Janisch (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2017)
We examine the long-run effects of forced migration from Eastern Europe into post-war Germany. Existing evidence suggests that displaced individuals are worse off economically, facing a considerably lower income and a higher unemployment risk than comparable natives even twenty years after being expelled. We extend this literature by investigating the relative performance of forced migrants across the entire life cycle. Using social security records that document the exact date of death and a proxy for pre-retirement lifetime earnings, we estimate a signifi cantly and considerably higher mortality risk among forced migrants compared to native West-Germans. The adverse displacement effect persists throughout the earnings distribution except for the top quintile. Although forced migrants are generally worse off regarding mortality outcomes, those with successful labor market histories seem to overcome the long-lasting negative consequences of flight and expulsion.
Keywords: I12; J61; O15; R23; 330; Forced Migration; Di erential Mortality; Lifetime Earnings; Economic History